2011
DOI: 10.1371/journal.pone.0026243
|View full text |Cite
|
Sign up to set email alerts
|

Dancing for Food in the Deep Sea: Bacterial Farming by a New Species of Yeti Crab

Abstract: Vent and seep animals harness chemosynthetic energy to thrive far from the sun's energy. While symbiont-derived energy fuels many taxa, vent crustaceans have remained an enigma; these shrimps, crabs, and barnacles possess a phylogenetically distinct group of chemosynthetic bacterial epibionts, yet the role of these bacteria has remained unclear. We test whether a new species of Yeti crab, which we describe as Kiwa puravida n. sp, farms the epibiotic bacteria that it grows on its chelipeds (claws), chelipeds th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
106
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 44 publications
(62 reference statements)
2
106
0
Order By: Relevance
“…Based on these observations, it has been hypothesized that S. crosnieri and K. puravida ingest their epibiotic microbial populations directly via this typical feeding behaviour, and digest them in their digestive organs (Watsuji et al, 2010;Thurber et al, 2011). In this study, we found setae fragments in almost every S. crosnieri intestine (Figure 1), which strongly suggests that the setae were ingested via the combing behaviour in S. crosnieri.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Based on these observations, it has been hypothesized that S. crosnieri and K. puravida ingest their epibiotic microbial populations directly via this typical feeding behaviour, and digest them in their digestive organs (Watsuji et al, 2010;Thurber et al, 2011). In this study, we found setae fragments in almost every S. crosnieri intestine (Figure 1), which strongly suggests that the setae were ingested via the combing behaviour in S. crosnieri.…”
Section: Discussionsupporting
confidence: 64%
“…The deep-sea vent galatheid crabs, S. crosnieri and K. puravida, frequently exhibit a typical behaviour where they comb their setae, which are covered with dense epibionts, using the third maxillipeds and then bringing the maxillipeds to the mouths, although this behaviour has not been observed in R. exoculata (Watsuji et al, 2010;Thurber et al, 2011). Based on these observations, it has been hypothesized that S. crosnieri and K. puravida ingest their epibiotic microbial populations directly via this typical feeding behaviour, and digest them in their digestive organs (Watsuji et al, 2010;Thurber et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the Crustacea, chemosynthetic epibioses are reported in only a few hydrothermal decapods: the shrimp Rimicaris exoculata (Segonzac et al, 1993), the galatheid crabs Kiwa hirsuta (Macpherson et al, 2005;Goffredi et al, 2008), Kiwa puravida (Thurber et al, 2011), and Shinkaia crosnieri (Miyake et al, 2007), and two amphipods from littoral sediments (Gillan and Dubilier, 2004; and sulphide-rich caves (Dattagupta et al, 2009). Most of these associations are regarded as nutritional ectosymbioses, but to date, there is little direct evidence of bacterial autotrophy and no direct demonstration of mutualistic nutritional bacteriahost interactions.…”
Section: Introductionmentioning
confidence: 99%